Digital Innovations in Convection Entrepreneurship Education Program for Youth Life Skills Development - Sri Nurhayati; Dadang Hermawan; Gumpanat Boriboon (IJECA (International Journal of Education and Curriculum Application), 2024)
The integration of digital innovations in education is crucial for enhancing teaching methodologies and improving student outcomes. In entrepreneurship education, digital tools can significantly enrich the learning experience by offering interactive and flexible environments. This research explores the implementation of digital innovations in the entrepreneurship education program at PKBM Saudara Sejiwa Bandung, identifies the challenges and opportunities, and examines the impact on participants' life skills and business development.  The study employed a case study approach, utilizing interviews with program participants, instructors, and managers. Data were collected on the use of digital tools, engagement with e-learning platforms, and the development of digital skills and business competencies. The data collected from interviews, observations, and documents were analyzed using thematic analysis. The research main findings are The use of WhatsApp facilitated communication and instruction, but digital design software and e-learning platforms were underutilized. Challenges included limited digital literacy, inconsistent internet access, and low e-learning engagement. However, opportunities such as increased confidence in digital tool usage, product innovation with DTF printing, and potential for e-commerce training were identified. Participants showed improved digital skills and confidence, with optimism for future business growth. The study highlights the need for enhanced digital infrastructure, comprehensive digital literacy training, and robust e-commerce support.